Clinical and virological features of acute hepatitis A during an ongoing outbreak among men who have sex with men in the North of France. (9th June 2018) - Boucher, Anne; Meybeck, Agnes; Alidjinou, Kazali; Huleux, Thomas; Viget, Nathalie; Baclet, Veronique; Valette, Michel; Alcaraz, Isabelle; Sauser, Eveline; Bocket, Laurence; Faiza, Ajana
Abstract : Objectives: Since February 2017, an increase of acute hepatitis A (AHA) cases has been notified in North of France. We aimed to report clinical and virological features of 49 cases treated in three hospitals in Lille European Metropolis (LEM). Methods: All adult patients treated for AHA in 3 LEM hospitals between 20 February and 5 July 2017 were included. Demographic characteristics, exposure risk factors to hepatitis A virus (HAV), AHA manifestations and concomitant sexually transmitted infections (STI) were retrospectively recorded. Results: Forty-nine cases of AHA were diagnosed among which 34 (69%) were hospitalised. Severe AHA occurred in 7 (14%) patients. The median age of cases was 36 years. All cases except 1 were men and 32 (65%) were identified as men having sex with men (MSM). Eleven (23%) patients were HIV-infected, 5 were under HIV pre-exposure prophylaxis (PrEP), 6 had a history of HIV postexposure prophylaxis and 19 had a history of at least one STI. Only three patients had received HAV vaccine. Proportion of patients tested for syphilis, chlamydial and gonococcal infections was 75% (18/24) in those seen by sexual health specialists and 21% (6/29) in those seen by other specialists. At least one concomitant STI was diagnosed in 13 out of 24 tested patients (54%). RT-PCR sequencing was available for 38 cases and confirmed co-circulation of 3 different strains of subgenotype IA (VRD 521 2016: n=24, RIVM-HAV16-090: n=13, V16-25801: n=1), already identified in several European countries. Conclusions: We are facing an outbreak of AHA among MSM in the North of France with a high rate of hospitalisation. Analysis of cases highlighted missed opportunities of vaccination and lack of concomitant STI screening. Awareness among healthcare providers and MSM should be increased and HAV vaccination promoted.